Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$$\begin{cases} \frac{dy}{dx} + 3y = 8, \\ y(0) = 0. \end{cases}$$

So, I have been getting an answer of $3$ by integrating and getting $\ln(8-3y) = x$ and solving. But my book says the answer must be expressed as a function of $x$. I do not know what to do.

share|improve this question
    
The standard procedure is: you find a particular solution to the ODE (in this case there is a constant solution), and the general solution to the corresponding homogeneous ODE, which here has the form $y = c*something(x)$. Then you find $c$ so c*something(0) + [particular solution](0) = 0$ –  Stefan Smith Oct 4 '12 at 21:42
    
This problem will admit separation of variables. –  Michael Hardy Oct 4 '12 at 22:16

4 Answers 4

You have $y'(x)+3y(x)=8\Rightarrow \mathbb{e}^{3x}y'(x)+3\mathbb{e}^{3x}y(x)=8\mathbb{e}^{3x}\Rightarrow \mathbb{e}^{3x}y'(x)+\left(\mathbb{e}^{3x}\right)'y(x)=8\mathbb{e}^{3x}\Rightarrow$

$\left(\mathbb{e}^{3x}y(x)\right)'=8\mathbb{e}^{3x}\Rightarrow {\Large\int}\left(\mathbb{e}^{3x}y(x)\right)'\;\mathbb{d}x={\Large\int}8\mathbb{e}^{3x}\;\mathbb{d}x\Rightarrow \mathbb{e}^{3x}y(x)=\frac{8}{3}\left(\mathbb{e}^{3x}\right)+c\Rightarrow $ *for $c\in\mathbb{R}$

$y(x)=\frac{8}{3}+\frac{c}{\mathbb{e}^{3x}}$, now since $y(0)=0\Rightarrow c=-\frac{8}{3}$ and $y(x)=\frac{8}{3}-\frac{8}{3\mathbb{e}^{3x}}$.

share|improve this answer

Multiply both sides of the differential equation by $e^{3x}$. This will give you $e^{3x}\dfrac{dy}{dx}+3 e^{3x}y=8e^{x}$, which is $$ \dfrac{d}{dx}(ye^{3x})=8e^{3x} $$ Integrate both sides with respect to x (don't forget to add a constant).

share|improve this answer
    
The method I described is a very common strategy to deal with this kind of problem. You can read more about it here: en.wikipedia.org/wiki/Integrating_factor –  Marra Oct 4 '12 at 21:47

$$ \int\frac{y'}{8-3y}dx=\int 1 dx\\ -\frac13\ln(8-3y)=x+c\\ 8-3y=e^{-3(x+c)}\\ y=-\frac13(e^{-3(x+c)}-8), $$ and with $y(0)=0$ you'll get $0=-\frac13(e^{-3c}-8)$, which gives $c=-\frac13\ln8$.

share|improve this answer

Write this as $dy/dx+3(y-8/3)$ and then integrate $dy/(y-8/3)+3dx=0$ to get $\ln(y-8/3)+3x=c$ so $y-3/8=Ke^{-3x}$; $y(0)=0$ so $K=-3/8$ and $y=3/8-3/8e^{-3x}$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.